POSYANDU CADRE BEHAVIOR TOWARDS IVA EXAMINATION AT THE WEST KUNDUR COMMUNITY HEALTH CENTER - Sudarsono Sudarsono; Roni Aldiano (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2020)
Background : In Indonesia, it is estimated that 15,000 new cases of cervical cancer occur each year, while the death rate is estimated at 7500 cases per year (Emilia, 2010). Frequent delays in treatment have resulted in many cervical cancer sufferers dying, even though cervical cancer can be treated if it has not reached an advanced stage, of course by knowing in advance whether it is infected or not by using several early detection methods, including the Pap smer method, IVA ( Visual Inspection with Acetic Acid), Thin Prep, and Colposcopy, vicography, papnet (computerized). (Nugroho, 2010). The purpose of this study was to determine the behavior of posyandu cadres towards iva examination at the Kundur barat public health center. Method : This research design is descriptive. The research was conducted at the West Kundur Community Health Center. Population is a generalization area consisting of objects (objects) / subjects (people) that have certain qualities and characteristics that are determined by the researcher for research and conclusions are drawn (Sulistyaningsih, 2011). In the study, the population was the posyandu cadres in the West Kundur Community Health Center (Puskesmas) as many as 214 cadres. In taking the sample in this study using purposive sampling technique, namely purposive sampling in accordance with the requirements / sample criteria required. The type of instrument used in this study was a questionnaire, in the form of a written question addressed to the respondent to be answered. Univariate analysis is used to explain or describe the characteristics of each variable under study by presenting a description of the frequency distribution. The instrument used for knowledge is a questionnaire, the form of questions used is a true or false statement for the assessment of the respondent's answer, if the respondent answers correctly each question item is given a value of 1 and if it is wrong it is given a value of 0. Result : The results and conclusions in this study are: know the behavior of posyandu cadres regarding IVA examinations at the West Kundur Puskesmas in 2018 the majority never conducted IVA examinations, namely 38 respondents (55.9%) out of 68 respondents. Congclusions : It is known that the behavior of posyandu cadres regarding the IVA examination at the West Kundur Puskesmas in 2018 the majority never conducted an IVA examination, namely as many as 38 respondents (55.9%) out of 68 respondents